The Renal System at a Glance / Second Edition - O'Callaghan Chris (Blackwell Publishing, 2006)
The book provides a concise and accessible introduction and revision aid for medical students. Preface, Abbreviations, Glossary, Introduction, Development of the Renal System, Clinical Features of Kidney Disease, Basic Renal Science, Renal Sodium Handling, The Kidney and Water Handling, Renal Vascular Biology, Renal Pharmacology: Diuretics, Disorders of Renal Metabolic Function, Hereditary Disorders of Tubular Transport, Disorders of Sodium and Water Metabolism, Regulation of Potassium Metabolism, Hypocalcemia and Hypercalcemia, Renal Disease Processes, Specific Diseases Affecting the Glomeruli, Tubulointerstitial Disease, Diabetes Mellitus and the Kidney, Polycystic Kidney Disease, Chronic Renal Failure and Renal Bone Disease, Clinical Cases, Index.